Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/sj.leu.2403043
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA mutations in primary leukemia cells after chemotherapy: clinical significance and therapeutic implications

Abstract: Mitochondrial DNA (mtDNA) codes for 13 respiratory chain subunits and is more vulnerable to damage than nuclear DNA due, in part, to a lack of histone protection and a weak repair capacity. While mtDNA alterations have been observed in human cancer, their roles in oncogenesis and chemosensitivity remain unclear. We investigated the relationship between mtDNA mutations, reactive oxygen species (ROS) generation, and clinical outcomes in chronic lymphocytic leukemia (CLL) patients. An analysis of mtDNA from 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
133
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 30 publications
7
133
0
Order By: Relevance
“…Mitochondria also have fundamental functions in energy metabolism, production of reactive oxygen species (ROS), and apoptosis (Carew et al, 2003). Apoptosis performs a vital function in cancer growth and in the cellular response to anticancer agents.…”
Section: Amino Acids Substitutions In Acute Lymphoblastic Leukemia Sumentioning
confidence: 99%
See 3 more Smart Citations
“…Mitochondria also have fundamental functions in energy metabolism, production of reactive oxygen species (ROS), and apoptosis (Carew et al, 2003). Apoptosis performs a vital function in cancer growth and in the cellular response to anticancer agents.…”
Section: Amino Acids Substitutions In Acute Lymphoblastic Leukemia Sumentioning
confidence: 99%
“…The percentage of heteroplasmy in mitochondrial genome within each may differ by the time. This type of mutation, which changes the mitochondrial DNA, would lead polymorphism between individuals within same family regardless of carrying the same pathogenic mtDNA mutation (Wallace, 1992;Carew et al, 2003).…”
Section: Amino Acids Substitutions In Acute Lymphoblastic Leukemia Sumentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, therapy-induced mutations were present at a low level. 4 Recently, Carew et al 5 reported a high mtDNA mutation rate in leukocytes of patients with chronic lymphatic leukemia (CLL) after chemotherapy. In this study, the mtDNA sequences of primary CLL cells were compared to the Cambridge reference sequence.…”
mentioning
confidence: 99%